AB0307 Assessment Asymptomatic Preclinical Rheumatoid Arthritis-Associated Interstitial Lung Disease with High Resolution CT and Pulmonary Function Tests. (9th June 2015) - Rekik, S.; Dhahri, R.; Boussaid, S.; Aouadi, A.; Ajlani, H.; Sahli, H.; Cheour, E.; El Euch, M.
Abstract : Background: Interstitial lung disease (ILD) is a common extra-articular manifestation of rheumatoid arthritis (RA) and a significant cause of morbidity and mortality. Objectives: The objective of this study was to define high-resolution chest CT (HRCT) and pulmonary function test (PFT) abnormalities to identify asymptomatic, preclinical forms of RA-ILD that may represent precursors to more severe fibrotic lung disease. Methods: Our study is prospective. We collect 20 RA patients with no respiratory functional sign. All patients met the 1987 diagnostic criteria of the American College of Rheumatology (ACR). We analyzed chest HRCTs in consecutively enrolled RA patients and subsequently classified these individuals as RA-ILD or RA-no ILD based on the presence/absence of ground glass opacification, septal thickening, reticulation, traction bronchiectasis, and/or honeycombing. Coexisting PFT abnormalities (reductions in percent predicted FEV1, FVC) were also used to further characterize occult respiratory defects. Results: Twenty patients were included in the study. Their demographic and clinical characteristics are summerized in the table below. In this study, all RA patients were treated with combinations of DMARDs and cortico steroids (7.5 mg per day) that included methotrexate (MTX), with a dose ranging from 10 to 15 mg (mean at 12.33 mg) per week; however, only 4.6% of RA patients used Leflunomide (20 mg per day). In terms of additional environmental risk factors, the prevalence of smoking was very low (1/20). Radiographic abnormalities are objectified in 4 cases 20% of cases. The most common abnormality is represented by interstitial syndrome found in 3 cases: diffuse reticulomicronodular images in 2 cases and pleural thickening in one case. The results of our study showed a restrictive syndrome in 5 cases (25%) and a mixed syndrome in 1 case (5%). Among the 13 patients with ILD on HRCT, only 4 have a restrictive syndrome. As regards the restrictive syndrome (CVF equal to 69% of the theoretical in both cases), corresponding HRCT was normal. In the case of mixed syndrome CT revealed centrolobular and para septal emphysema predominantly in the bi upper lobe. Conclusions: HRCT represents an effective tool to detect occult/asymptomatic ILD that is highly prevalent in our unselected, university-based cohort of RA patients. Disclosure of Interest: None declared